Perbedaan Kemampuan Menggiring Bola Antara Kelompok Rangkaian Bermain dan Rangkaian Latihan Siswa - Nurmayasni Nurmayasni (JPGI (Jurnal Penelitian Guru Indonesia), 2019)
Based on researchers' observations of the phenomena that occur in students at SDN 44 Taratak, Koto XI Tarusan sub-district, the ability to dribble is relatively low. This problem is thought to be caused by several factors, one of which is the inadequate training method provided by the trainer. This study aims to explain the effect of play and training sequences on dribbling skills at SDN 44 Taratak, Koto XI Tarusan District. This research method is a quasi-experimental method. This research will be conducted in December 2018. The research site is in the field of SDN 44 Taratak, Koto XI Tarusan sub-district. The study population numbered 20 people. The sampling technique was taken with a total sampling to obtain a sample of 20 athletes. The dribbling test data is taken with the dribbling test. The data analysis technique is the t test formula. The results of the data analysis show that: (1) there is playing a significant effect on the ability to dribble. Increased dribbling ability is 7.73, from an average score of 34.00 in the pre test to 26.63 in the post test. (2) The training sequence has a significant influence on the ability to shake the ball. The influence exerted was 8.09 from 34.05 when the achievement was 25.96 during the post test. (3) With tcount (0.675)> ttable (2.222), this means that the research hypothesis is not accepted. Thus it can be concluded that there is no difference in the influence of the playing sequence and the training sequence on the ability to dribble.